Asymmetric acyl-transfer promoted by readily assembled chiral 4-N,N-dialkylaminopyridine derivatives - CONNON, STEPHEN; MC CABE, THOMAS; WATSON, GRAEME WILLIAM (Royal Society of Chemistry, 2006)
The development of a new class of chiral 4-N,N-dialkylaminopyridine acyl-transfer catalysts capable of exploiting both van der Waals (?) and H-bonding interactions to allow remote chiral information to stereochemically control the kinetic resolution of sec-alcohols with moderate to excellent selectivity (s = 6?30). Catalysts derived from (S)-?,?-diarylprolinol are considerably superior to analogues devoid of a tertiary hydroxyl moiety and possess high activity and selectivity across a broad range of substrates.
PUBLISHED
Keywords: Biochemistry; Catalysts